Size Distribution of Airborne Particle-Bound Polybrominated Diphenyl Ethers and Its Implications for Dry and Wet Deposition - Luo, Pei; Ni, Hong-Gang; Bao, Lian-Jun; Li, Shao-Meng; Zeng, Eddy Y. (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2014)
Size distribution of particles in part dictates the environmental behavior of particle-bound organic pollutants in the atmosphere. The present study was conducted to examine the potential mechanisms responsible for the distribution of organic pollutants in size fractionated particles and their environmental implications, using an e-waste recycling zone in South China as a case study. Size-fractionated atmospheric particles were collected at the heights of 1.5, 5, and 20 m near two residential apartments and analyzed for polybrominated diphenyl ethers (PBDEs). The concentrations of particle-bound SPBDE (sum of 18 PBDE congeners) were significantly greater at 5 and 20 m than those at 1.5 m. The size-fractionated distributions of airborne SPBDE displayed trimodal peaks in 0.10-0.18, 1.8-3.2, and 10-18 mu m at 1.5 m but only an unimodal peak in 1.0-1.8 mu m at 20 m height. Emission sources, resuspension of dust and soil, and volatility of PBDEs were important factors influencing the size distribution of particle-bound PBDEs. The dry deposition fluxes of particle-bound PBDE estimated from the measured data in the present study were approximately twice the estimated wet deposition fluxes, with a total deposition flux of 3000 ng m-2 d(-1). The relative contributions of particles to dry and wet deposition fluxes were also size-dependent, e.g., coarse (aerodynamic diameters (D-p) > 1.8 mu m) and fine (D-p < 1.8 mu m) particles dominated the dry and wet deposition fluxes of PBDEs, respectively.